Fatigue behaviour of Inconel 625 cold spray coatings. (4th May 2018) - Cavaliere, Pasquale; Perrone, Angelo; Silvello, Alessio
ABSTRACT: Cold spray coatings were produced with Inconel 625 powders sprayed on a heat-treated Inconel 718 substrate. The processing parameters were varied to analyse the microstructural and mechanical variations as a function of cold spray conditions. Cold spray can contribute to improve the fatigue properties of repaired components; the best process conditions, leading to low porosity and high adhesion strength, were employed to produce coatings in notched samples to evaluate the fatigue crack behaviour of the sprayed material. The coatings were heat treated to evaluate the material microstructural evolution and mechanical properties. The crack initiation and growth behaviour of the coatings was studied also for the solution and precipitation hardening heat treatment condition to compare the fatigue behaviour with that belonging to the as sprayed one. It was demonstrated that the heat treatment has a beneficial effect on fatigue cracks retardation.